Balance and falls risk in women with lowr limb osteoarthritis or rheumatoid arthritis. - Hill, Keith; Williams, Sue; Chen, Jing; Moran, Helen; Hunt, Susan; Brand, Caroline (Elsevier Taiwan LLC., 2013)
Background/Purpose Lower limb arthritis is a risk factor for falls, although few studies have used comprehensive balance assessment to determine the degree to which this contributes to falls risk. This study evaluated the falls risk and balance impairment of women with lower limb osteoarthritis (OA) or rheumatoid arthritis (RA). Methods A cross-sectional comparative study was conducted of women living in the general community. Seventeen women with lower limb OA [mean age: 66.9 years, standard deviation (SD) = 9.8 years], 17 with lower limb RA (mean age: 66.3 years, SD = 9.4 years), and 17 age-matched healthy (no lower limb arthritis) women (mean age: 66.3 years, SD = 10.1 years) were recruited. All participants underwent a comprehensive balance and mobility assessment, including clinical balance measures (Step Test, Functional Reach), self-generated (Neurocom Balance Master long plate), and externally generated (Chattecx Balance System) force platform measures. Falls risk was assessed using the Falls Risk for Older People – Community version (FROP-Com). Results Sixty-five percent of the OA and 65% of the RA women reported one or more falls in the preceding 12 months, and both groups had significantly higher falls risk (FROP-Com) than the matched sample (p < 0.001). Both OA and RA participants had significantly impaired balance and mobility, lower activity level, and lower falls efficacy after adjustment for multiple comparisons, compared to the matched sample. Although women with RA performed worse on the majority of measures than the OA women, the difference was only significant for the Maximum Excursion measure of the Limits of Stability test. Conclusions Women with lower limb OA or RA have mild to moderate falls risk and balance impairments in comparison to age-matched older women. Further research is needed to evaluate whether exercise programs targeting balance performance, and other interventions to address their multiple falls risk factors, can improve balance and reduce falls in these clinical groups.